Molecular and epigenetic markers as promising tools to quantify the effect of occupational exposures and the risk of developing non-communicable diseases - Ferrari, Luca; Pavanello, Sofia; Bollati, Valentina (La Medicina del Lavoro, 2019)
Non-communicable diseases (NCDs) are chronic diseases that are by far the leading cause of death in the world. Many occupational hazards, together with social, economic and demographic factors, have been associated to NCDs development. Genetic susceptibility or environmental exposures alone are not usually sufficient to explain the pathogenesis of NCDs, but can be integrated in a more complex scenario that can result in pathological phenotypes. Epigenetics is a crucial component of this scenario, as its changes are related to specific exposures, therefore potentially able to display the effects of environment on the genome, filling the gap between genetic asset and environment in explaining disease development. To date, the most promising biomarkers have been assessed in occupational cohorts as well as in case/control studies and include DNA methylation, histone modifications, microRNA expression, extracellular vesicles, telomere length, and mitochondrial alterations.